Extrusion printing of a designed three-dimensional YBa2Cu3O7−x superconductor with milled precursor powder. Issue 13 (21st March 2017) - Wei, Xiangxia; Peng, Erwin; Xie, Yanyou; Xue, Junmin; Wang, John; Ding, Jun
Abstract : Designed milled YBCO hollow structures with high density, good mechanical properties and enhanced magnetization can prolong levitation time over magnets. Abstract : It is well known that bulk YBa2 Cu3 O7− x superconductors can carry transport current in a high magnetic field for many practical engineering applications. In this paper, three-dimensional YBCO parts with flexible shapes, high density and good superconducting properties were first successfully prepared by an extrusion-based additive manufacturing technique involving aqueous and non-aqueous pastes composed of milled precursors. The obtained milled powder can effectively reduce the sintering temperature and simultaneously improve densification of YBCO compared with the unmilled sample. Then, the milled powder dispersed in aqueous and non-aqueous systems was printable to build the YBCO part layer by layer, exhibiting shear thinning behaviors with the viscosity, density and porosity mainly related to the binder type and solid loading. It was found that non-aqueous PVB solution and high solid loading seemed to have a slightly positive effect on density, reaching up to 93% of theoretical density after just sintering at 940 °C for 10 h. To the end, a printed YBCO hollow cylinder with a large trapped magnetic field demonstrated its ability to prolong the levitation time, extending the potential application in flywheel technology. The integration of the extrusion printing technique with milled precursors realizes the possibility of producing complex-shaped and scale-up YBCO with useful electromagnetic properties for a broad range of applications.